2019
DOI: 10.1002/nafm.10261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Translocation Sites for an Imperiled Cyprinid, the Hornyhead Chub

Abstract: Translocation of isolated species into suitable habitats may help to secure vulnerable, geographically limited species. Due to the decline of Wyoming Hornyhead Chub Nocomis biguttatus, conservation actions, such as the translocation of populations within the plausible historical range, are being considered to improve population redundancy and resiliency to disturbance events. Translocation of Wyoming Hornyhead Chub must be rigorously evaluated because a hatchery stock does not exist, so all fish used in transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Previous research on the Laramie River suggested that low summer discharge was one factor limiting Hornyhead Chub distribution (Bestgen ). However, our research occurred during a period of relatively high and stable flows, primarily regulated by diversions, and discharge was not found to be an important limiting factor (Hickerson and Walters ). In general, a comparison between Laramie River sites with and without Hornyhead Chub found that differences in the fish communities were much greater than differences in habitat (Hickerson and Walters ).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous research on the Laramie River suggested that low summer discharge was one factor limiting Hornyhead Chub distribution (Bestgen ). However, our research occurred during a period of relatively high and stable flows, primarily regulated by diversions, and discharge was not found to be an important limiting factor (Hickerson and Walters ). In general, a comparison between Laramie River sites with and without Hornyhead Chub found that differences in the fish communities were much greater than differences in habitat (Hickerson and Walters ).…”
Section: Discussionmentioning
confidence: 92%
“…However, our research occurred during a period of relatively high and stable flows, primarily regulated by diversions, and discharge was not found to be an important limiting factor (Hickerson and Walters ). In general, a comparison between Laramie River sites with and without Hornyhead Chub found that differences in the fish communities were much greater than differences in habitat (Hickerson and Walters ). The fish community data suggest that the low abundance of Hornyhead Chub in the lower reach coincides with the upstream invasion of Smallmouth Bass (Quist et al.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Multivariate analysis.-We assessed dissimilarity in habitat and fish communities among the 2018-2019 study sites by using nonmetric multidimensional scaling (NMDS; Kenkel and Orlóci 1986) following Hickerson and Walters (2019) with the vegan package (Oksanen et al 2019) in R (R Core Team 2019). Fish community data ordination was performed using the Jaccard dissimilarity index (Cha 2007) with binary species occurrence data.…”
Section: Methodsmentioning
confidence: 99%